Pengembangan Media Permainan Game Kotak Alphabet Berbasis Android Untuk Meningkatkan Keterampilan Pengenalan Huruf Pada Anak Usia Dini - Jusmadi, Evryeni (Publikasi Indonesia, 2025)
The objectives of this study are to: (1) develop android-based alphabet box game media to improve letter recognition skills in early childhood (2) describe the effectiveness of android-based alphabet box game media to improve letter recognition skills in early childhood. The subjects of this study were 25 children aged 5-6 years from Bina Belia Kindergarten, Jl. Raya Tanjung Agung, Tanjung Agung Village, Ulu Musi District, Empat Lawang Regency, the focus of this research is an android-based alphabet box game media to improve letter recognition skills in early childhood. This research was conducted with a